The PICOHIDRO POWER ELECTRIC PLANT DESIGN IS EQUIPPED BY ELECTRONIC CONTROL SYSTEM (ECU) - Prasetyo, Budi; Pradigdo, Dedy; Diantoro, Indra (Pustaka Poltekad, 2021)
Abstrak: There are many streams of water or rivers around us which are felt to be underutilized effectively. Therefore, it is necessary to develop Pico hydro technology as an alternative to power generation. Pico hydro usually produces low wattage so that it is not optimal for people to use in their daily lives. Therefore, the design of a power plant is designed that is equipped with an ECU control system as a water source control system that can produce greater electrical energy. The research method used is a pure experimental method to find out the results obtained are 300 watts by calculating the pressure sent to the ECU system. Technically, Pico hydro has several components in it, such as waterwheel water as a turbine, steering blade and generator. Pico hydro can be used as an alternative energy that utilizes the flow of water which can be used as an energy source. The Pico hydro generator used in this study is the Brantas River in Pendem Village, Karangploso District, Batu Malang City. With adequate water flow, using a Francis type water turbine, and using a 200Watt generator and controlled by the ECU system. From the test results obtained potential energy of 5880 (Nm), compressive energy of 2.107 (N/m2) pipe flow velocity (v) 7.668 (m/s) energy contained in water 45.67 (watts) Francis turbine efficiency 31.97% generator efficiency is 28.77% and the maximum power produced by a 200 watt generator is 29Volt